PERTIMBANGAN HUKUM HAKIM PRAPERADILAN DALAM PENGHENTIAN PENYIDIKAN: ANALISIS PUTUSAN NOMOR 9/PID.PRA/2024/PN.BGL: Judicial Legal Considerations In Pre-Trial Decisions Regarding The Termination Of Investigations: Analysis Of Decision Number 9/Pid.Pra/2024/Pn.Bgl - Nadiyah Yusuf; Setiyono (Reformasi Hukum Trisakti, 2026)
Pretrial proceedings are a supervisory mechanism within the criminal justice system that aims to protect the rights of suspects from arbitrary actions by law enforcement officials. However, in practice, issues often arise regarding the limits of the pretrial judge's authority, particularly regarding the existence of a dictum or order (condemnatoir) to terminate an investigation. The research problem formulation in this study is whether the legal considerations of the pretrial judge in the Bengkulu District Court (PN) Decision Number 09/Pid.Pra/2024/PN.Bgl which terminated the investigation are in accordance with the provisions of the Criminal Procedure Code (KUHAP). The research method used is normative juridical with a statutory regulatory approach and case studies, through an analysis of the KUHAP and the Constitutional Court Decision Number 21/PUU-XII/2014. The results of the study indicate that the pretrial judge's authority should be limited to testing the validity of the investigator's actions, not taking over the authority to terminate the investigation, which is normatively attributed to the investigator. This decision substantively protects the suspect's rights, but is not fully in line with the principles of legality and legal certainty.